Enhancing capillary trapping effectiveness through proper time scheduling of injection of supercritical CO2 in heterogeneous formations. Issue 2 (23rd November 2016) - González‐Nicolás, Ana; Trevisan, Luca; Illangasekare, Tissa H.; Cihan, Abdullah; Birkholzer, Jens T.
Abstract: The impact of geologic heterogeneity on capillary trapping of supercritical CO2 (scCO2 ) has been recognized and appraised through laboratory experimentation and modeling. However, how different injection strategies can be optimized to improve capillary trapping has not received adequate attention. We present a study based on stochastic analysis to show the impact of injection scheduling on capillary trapping of scCO2 in heterogeneous geological formations. Improvement of trapping efficiency consists of maximizing the trapped volume within a predefined secure zone of the storage formation with the goal of avoiding plume intersection with potential leakage pathways. Using knowledge acquired from physical experiments in intermediate‐scale tanks with controlled heterogeneity, we conduct numerical simulations following a stochastic approach to extend the observed outcomes to a series of equally probable permeability scenarios. Our simulations involve the same combination of surrogate fluids that are used in the experiments to mimic viscosity and density contrasts between scCO2 and brine. To account for uncertainty of formation heterogeneity, several permeability fields with three different variances and two horizontal correlation lengths are generated. The same volume of scCO2 is emplaced using four different modes of injection scheduling. Results suggest that injection strategies aimed at enhancing capillary trapping of scCO2 and increasing the probability of constraining the plume within a secure zone are strictly related to the specific heterogeneity of the reservoir. This preliminary theoretical finding suggests the potential for maximizing secure capillary trapping through the proper selection of injection schedule to fit the formation heterogeneity. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd.